IN VITRO AND IN VIVO ANTIANGIOGENIC EFFECT OF ARTOCARPUS HETEROPHYLLUS SEED EXTRACT - M, Thiruselvi; Durairaj, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Angiogenesis the formation of new blood vessels from the pre-existing vasculature plays a major role in tumor growth, invasion, and metastasis of cancer diseases. The current research was designed for the inhibition of angiogenesis, which can provide a novel way to inhibit tumor growth and metastasis in cancer. Methods: The antiangiogenic properties of serial concentrations of the hydroethanolic extract of Artocarpus heterophyllus were examined in human umbilical vein endothelial cells (HUVECs) using a tube formation assay in vitro and in a Matrigel plug assay as in vivo model. Results: Hydroethanolic extract of A. heterophyllus significantly inhibited vascular endothelial growth factor (VEGF)-mediated angiogenesis in the HUVECs in culture dose-dependently. Further, the new blood vessel formation was observed to be inhibited by the extract at 100 mg/kg p.o. in Matrigel plug model in C57BL/6 mice. However, the effect was enhanced in higher concentration (500 mg/kg p.o.) demonstrating the in vivo antiangiogenic activity of the extract. Conclusion: This study demonstrated that the hydroethanolic seed extract of A. heterophyllus strongly inhibited the angiogenesis in HUVECs. Moreover, the extract significantly inhibited the VEGF production in HUVECs, confirming their possible antiangiogenic mechanism.